Employing a Model Based Conceptual Design Approach to Design for Resilience. Issue 1 (20th September 2021) - Flanigan, David; Robinson, Kevin
Abstract: During the development of a conceptual system, it is common to address the capability gaps or create additional capabilities in the system concept. The Model Based Conceptual Design (MBCD) approach can be helpful to identify, catalogue, trace, and develop these capabilities, particularly as they cross different domains. This paper explores the use of MBCD to insert and improve resilience within an existing MBCD schema. An approach is offered to evaluate how resilience may be viewed and analyzed by using an MBCD approach.